Potencial enólogico das uvas Touriga nacional e Petit Verdot na safra 2021 em Dom Pedrito. - Ferreira, Bianca da Fonseca (2021)
The Gaucha Campaign located in the pampa biome has unique characteristics, it is the second largest producer of fine wines in Brazil. In 2020, a major milestone was achieved, the achievement of the Indication of Origin seal of the Gaucha Campaign, demonstrating its quality. This indication includes 36 varieties, including Petit Verdot and Touriga Nacional, two varieties that adapt to different types of soil, give origin to wines of intense color, can be consumed young or for aging. This work aimed to evaluate the oenological suitability of the cultivars Touriga Nacional and Petit Verdot in the municipality of Dom Pedrito. In this context, a vinification of traditional red wines was carried out, followed by analysis of chromatic parameters (color intensity, free anthocyanins, total polyphenols) by spectrophotometry, in addition to physical chemical analysis, alcohol, total acidity, glycerol, sugar, malic acid and lactic acid to check if the wines are within the quality and identity standards defined by Brazilian legislation. Sensory analysis of the wines was also carried out to assess their quality. The statistical treatment of the collected data included the determination of the mean and standard deviation between biological and analytical replicas. It can be observed in both wines a good alcoholic content 12% V/V, pH 3.5 and 3.6 within the normal range, the reducing sugar content, below 4 which indicates that the wine is dry, the acid content malics and lactics show that both wines performed malolactic fermentation. It is concluded that both wines have good oenological potential, fit within the Brazilian legislation and are wines of good sensory quality.